1996
DOI: 10.1097/00007632-199603150-00019
|View full text |Cite
|
Sign up to set email alerts
|

Dose Distribution at Radiographic Examination of the Spine in Pediatric Radiology

Abstract: Thoracic spine and lumbar spine examinations lead to relatively high-absorbed doses to radiation-sensitive organs. Because the scoliosis investigation is repeated several times, the total effective dose could be considerable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 18 publications
0
14
0
1
Order By: Relevance
“…The Cobb method has been used to assess the progression of the curvatures, to select the types of interventions, and to assess their effectiveness (Weinstein and Buckwalter, 2000). However, health professionals worry regarding the amount of radiation imposed on these adolescents during the follow-up assessments (Almén and Mattsson, 1996;Levy et al, 1996). This is because, in some cases, X-rays from the anterioreposterior (AP) and the lateral views, need to be performed every three months (Weiss et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The Cobb method has been used to assess the progression of the curvatures, to select the types of interventions, and to assess their effectiveness (Weinstein and Buckwalter, 2000). However, health professionals worry regarding the amount of radiation imposed on these adolescents during the follow-up assessments (Almén and Mattsson, 1996;Levy et al, 1996). This is because, in some cases, X-rays from the anterioreposterior (AP) and the lateral views, need to be performed every three months (Weiss et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…One study compared conventional film/grid technique (F/G) with air-gap technique using computed radiography (CR) [12], two studies [17,18] used an air-gap technique using conventional films and the other three studies performed the scoliosis examinations by digital-pulsed fluoroscopy [14,16,19]. In four of these studies, the effective doses were determined based on the Monte Carlo calculation using PCXMC or a similar computer program [12,14,16,18], whereas the estimation in two analyses involved calculating the total energy transfer to the organs, based on air kerma or TLD measurements [17,19]. Although there is no accepted standard method for the determination of the effective radiation doses of radiological procedures in children, Geijer H. et al [16] found a remarkably good correlation between the measured values of effective dose and the Monte Carlo calculations which indicates that these calculations are a useful tool in the clinical setting for the evaluation of the effective dose.…”
Section: Discussionmentioning
confidence: 99%
“…Hansen et al (2003) reported greater Ka,e values for the same agedefined groups, mainly due to the fact that an antiscatter grid was used, contrary to that found in this study. A significant exception was the study of Almen and Mattsson (1996a) where a large FFD technique (FFD ϭ 4.1 m, with air-gap ϭ 20 cm) was used instead of a grid, which resulted in smaller Ka,e.…”
Section: Entrance Surface Kerma Kaementioning
confidence: 99%